Herder's political thought : a study of language, culture, and community - Spencer, Vicki A., 1961- (University of Toronto Press, 2012)
"Johann Gottfried Herder was a philosopher and important intellectual presence in eighteenth-century Germany. Herder's Political Thought examines the work of this significant figure in the context of both historical and contemporary developments in political philosophy.
Keywords: Herder, Johann Gottfried, -- 1744-1803 -- Contributions in political science.; Herder, Johann Gottfried, -- 1744-1803 -- Criticism and interpretation.; Herder, Johann Gottfried, -- 1744-1803; Political science -- Philosophy -- History -- 18th century.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Political science; Political science -- Philosophy; 1700-1799; Criticism, interpretation, etc.; History